Analysis of MCLP, Q-MALP, and MQ-MALP with Travel Time Uncertainty Using Monte Carlo Simulation - Abdul Ghani, Noraida; Ahmad, Norazura (Hindawi Publishing Corporation, 2017)
This paper compares the application of theMonte Carlo simulation in incorporating travel time uncertainties in ambulance location problem using three models: Maximum Covering Location Problem (MCLP), Queuing Maximum Availability Location Problem (Q-MALP), andMultiserver QueuingMaximum Availability Location Problem (MQ-MALP). A heuristic method is developed to site the ambulances.The models are applied to the 33-node problem representing Austin, Texas, and the 55-node problem. For the 33-node problem, the results showthat the servers are less spatially distributed in Q-MALP andMQ-MALPwhen the uncertainty of server availability is considered using either the independent or dependent travel time. On the other hand, for the 55-node problem, the spatial distribution of the servers obtained by locating a server to the highest hit node location is more dispersed inMCLP and Q-MALP.The implications of the new model for the ambulance services system design are discussed as well as the limitations of the modeling approach.